(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
In The Sufferings of Young Werther, Goethe, along with his literary, aesthetic, religious and philosophical views, highlighted political, social and legal problems. In them, the young Goethe recognized that the truth of the heart is above any paper, law and rules, and human justice is above the rules and laws written by members of society. The article talks about this.